Digital Marketing Through Instagram Ads: A Case Study of “Instaboost Life” Instagram - Ayu Sulistya Putri Sugeng; Juni Alfiah Chusjairi (Research Synergy Foundation, 2022)
This study concerns a small medium enterprise called “ Instaboost Life”. Instaboost Life is an online shop that sells healthy products such as slimming tea, beverages for mothers who are breastfeeding, lemon beverages, and other healthy beverages that are healthy and safe for diet. Due to their high price, the products are highly likely to be consumed by middle-class people. As an online shop, the products are merely for sale online. Therefore, social media is used to promote the products, which in this case is Instagram. The aim of this research is to identify whether more advertising on Instagram raises more potential buyers and finally make a purchase decision. The data collected in this research is internal data from Instaboost Life from January-June 2021 and 5 interviews with users of Instaboost Life. After analyzing the data, the authors conclude that more budget spending plays a significant role in reaching the targeted audience and potential buyers. Furthermore, their decision to purchase order. In addition, the interviewees also confirmed that advertising played a significant role in their decision to purchase order products from Instaboost Life.